2023
DOI: 10.1093/ibd/izad012
|View full text |Cite
|
Sign up to set email alerts
|

Delays in Therapy Associated With Current Prior Authorization Process for the Treatment of Inflammatory Bowel Disease

Abstract: Lay Summary Despite a high approval rate, there were unnecessary delays in therapy due to prior authorizations. This study identified the impact of type of IBD, FDA-labeled indication, and dose escalations on approvals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Prior surveys regarding PAs, including a 2021 survey by the American Medical Association, noted that 93% of physicians reported PAs led to delays in care, 90% saw a negative impact on clinical outcomes, and 34% experienced PA denials resulting in a serious adverse event. 3 , 7 Furthermore, in cases of therapy abandonment, 87% were due to PAs, and 30% of PA requisites were rarely or never evidence-based. 7 Studies have also shown that having an FDA-labeled indication increases the likelihood of PA approval and dose escalation requests had the lowest rates of approval, which complicates the requests for nonstandard dosing for patients who experience partial or loss of response to therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior surveys regarding PAs, including a 2021 survey by the American Medical Association, noted that 93% of physicians reported PAs led to delays in care, 90% saw a negative impact on clinical outcomes, and 34% experienced PA denials resulting in a serious adverse event. 3 , 7 Furthermore, in cases of therapy abandonment, 87% were due to PAs, and 30% of PA requisites were rarely or never evidence-based. 7 Studies have also shown that having an FDA-labeled indication increases the likelihood of PA approval and dose escalation requests had the lowest rates of approval, which complicates the requests for nonstandard dosing for patients who experience partial or loss of response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 7 Furthermore, in cases of therapy abandonment, 87% were due to PAs, and 30% of PA requisites were rarely or never evidence-based. 7 Studies have also shown that having an FDA-labeled indication increases the likelihood of PA approval and dose escalation requests had the lowest rates of approval, which complicates the requests for nonstandard dosing for patients who experience partial or loss of response to therapy. 7 …”
Section: Discussionmentioning
confidence: 99%
“… 18 A subsequent adult study of 1693 authorizations showed similar delays of a median 11 [interquartile range (IQR): 6–20] days, but the length of delay increased with each level of appeal that was required [first appeal: 29 (IQR: 17–48) days; second level appeal: 51 (IQR: 27–84) days; external review: 73 (IQR: 28–98) days]. 19 A quality improvement initiative within 18 adult IBD providers aimed at improving time-to-biologic- and small-molecule administration found that the insurance approval process step was not improved and actually lengthened over time despite their shortening time to medication administration by 4 days through streamlined internal processes. 20 Within the pediatric study, they examined the impact of medication delays on IBD-related healthcare utilization within 6 months from the delay, and those who required prior authorization had a 13% (95% CI: 2.5–23.4) increase in healthcare utilization after adjusting for demographics and disease-severity characteristics.…”
Section: Barriers To Care For Patients With Ibdmentioning
confidence: 99%
“…Payors and physician benefit managers do not. Recent publications highlight several issues, including specific to inflammatory bowel disease (IBD), on how insurance/payor delays lead to increased health care utilization, steroid dependence, and administrative time (1–3). While Choi et al (1) reported 97% of requests do get approved, the current system does not benefit the consumer and might even lead to adverse events.…”
Section: Dear Editormentioning
confidence: 99%